Microplastic testing in vitro: realistic loading of pollutants, surfactant-free solid surface-dosing and bioanalytical detection using a sensitivity-optimized EROD assay - Heinrich, Patrick; Braunbeck, Thomas (Toxicology in vitro, 2019)
Microplastic particles (MPs) are emerging contaminants in aquatic environments, which are assumed to play a role as vectors for lipophilic pollutants, as the particles bear a potential for the accumulation of lipophilic contaminants from the water phase on the MPs' surface and subsequent release in contact with organisms. In an attempt to allow the bioanalytical detection and quantitatively estimate bioavailability of MP-bound pollutants under realistic conditions in vitro, a protocol was developed for water-based loading of lipophilic substances to MPs using a solid-phase extraction (SPE) approach and subsequent detection of the substances in a sensitivity-enhanced 7-ethoxyresorufin-O-deethylase (EROD) assay with RTL-W1 cells. Exemplarily, particles were loaded with benzo[k]fluoranthene (BkF), which was shown to bind to MPs with high affinity. Spiked particles were added to the surface of the culture medium, where they released low, but consistent amounts of BkF, which were quantified by EROD induction. Additionally, a geometrical model was developed for the estimation of numbers, surface areas and masses of MPs interacting with medium. The approach presented allows the experimental in vitro examination of the postulated function of MP as a pollutant vector in a highly sensitive animal-experimentation-free test system.